Pre-clinical Mouse Models of Neurodegenerative Lysosomal Storage Diseases - Favret, Jacob M.; Weinstock, Nadav I.; Feltri, M. Laura; Shin, Daesung (Frontiers in Molecular Biosciences, 2020)
There are over 50 lysosomal hydrolase deficiencies, many of which cause neurodegeneration, cognitive decline and death. In recent years, a number of broad innovative therapies have been proposed and investigated for lysosomal storage diseases (LSDs), such as enzyme replacement, substrate reduction, pharmacologic chaperones, stem cell transplantation, and various forms of gene therapy. Murine models that accurately reflect the phenotypes observed in human LSDs are critical for the development, assessment and implementation of novel translational therapies. The goal of this review is to summarize the neurodegenerative murine LSD models available that recapitulate human disease, and the pre-clinical studies previously conducted. We also describe some limitations and difficulties in working with mouse models of neurodegenerative LSDs.